Skin fold thickness and its association with milk production performance in Sahiwal cows - BANJARE, SWETA; SANTRA, AJIT KUMAR; PARVEEN, KAISER; MISHRA, SHARAD; SINGH, NISHIMA (The Indian Journal of Animal Sciences, 2025)
The present experiment was conducted at Bull Mother Experimental Farm (BMEF), College of Veterinary Science and Animal Husbandry, Anjora to study the relationship between skin thickness and milk yield of Sahiwal cows. The overall mean skin thickness of neck, dewlap, chest, abdomen, flank, hind quarter, udder and rump was 3.44±0.06, 3.49±0.06, 3.53±0.06, 4.53±0.08, 5.62±0.12, 4.07±0.07, 2.45±0.04 and 6.63±0.17 mm respectively. Analysis of variance showed that that the effect of skin thickness was statistically significant (P